(untitled) (Texas Journal of Engineering and Technology, 2023)
In the article, different biomass raw materials and hydrocarbon waste processing methods are studied. The authors proposed the principle thermal scheme of the auger drum pyrolysis device, and the prototype was installed at the “Alternative energy sources” training ground of the Karshi Engineering Economics Institute, and preliminary thermal and technical tests were conducted. According to the results of the conducted experimental research, as a result of pyrolysis processing of biomass raw materials and various hydrocarbon waste: from solid household waste (unsorted) up to 35-60%, from car tires and other rubber waste up to 45-60%, from medical waste 25-30%, 25-30% from wood and agricultural waste, 45- 65% from all types of plastic are indicated